Vascular Endothelial Growth Factor, Irradiation, and Axitinib Have Diverse Effects on Motility and Proliferation of Glioblastoma Multiforme Cells - Krcek, Reinhardt; Matschke, Veronika; Theis, Verena; Adamietz, Irenäus Anton; Bühler, Helmut; Theiss, Carsten (Frontiers in Oncology, 2017)
Glioblastoma multiforme (GBM) is the most common primary brain tumor. It is highly aggressive with an unfavorable prognosis for the patients despite therapies including surgery, irradiation and chemotherapy. One important characteristic of highly vascularized GBM is the strong expression of vascular endothelial growth factor (VEGF). VEGF has become a new target in the treatment of GBM, and targeted therapies such as the VEGF-receptor blocker axitinib are in clinical trials. Most studies focus on VEGF-induced angiogenesis, but only very few investigations analyze autocrine or paracrine effects of VEGF on the tumor cells. In this study we examined the impact of VEGF, irradiation, and axitinib on cell proliferation and cell motility in human glioblastoma multiforme cell lines U-251 and U-373. VEGF-receptor 2 was shown to be expressed within both cell lines by using PCR and immunochemistry. Moreover, we performed 24-hour videography to analyze motility, and a viability assay for cell proliferation. We observed increasing effects of VEGF and irradiation on cell motility in both cell lines, as well as strong inhibiting effects on cellular motility by VEGF-receptor blockade using axitinib. Moreover, axitinib diminished irradiation induced accelerating effects. While VEGF stimulation or irradiation did not affect cell proliferation, axitinib significantly decreased cell proliferation in both cell lines. Therefore, the impairment of VEGF signaling might have a crucial role in the treatment of GBM.